Analisa Turbine Crossflow Mini Microhidro dengan Variasi Blade menggunakan Simulasi CFD - Yolanda, Rizky Prima; Finahari, Nurida; Wicaksono, Leo Hutri (PROTON, 2023)
The need for electricity is very important in the current era. However, there are still areas in Indonesia that have not received electricity, and there are also areas that have received electricity but experience rolling blackouts for several days a week. To overcome this, an alternative power plant is needed, namely a mini micro hydro power plant. The turbine in this power plant is able to function with water discharge below 10 meters, but can produce electrical power above 600 W to meet the electricity needs of each house adjacent to the water source. Given the natural resources (water sources) that are still abundant, it is unfortunate if they cannot be utilized properly. Another interesting factor of this mini-microhydro power plant is that the technology is relatively simple, and easily applied to areas that have mountainous topography and many rivers. In the process of making turbines, simulation steps are needed in the experiment so that it does not require a lot of money in the experiment, but produces a design that has high efficiency. From the analysis of the design simulation results, it can be concluded that the mini micro hydro crossflow turbine with 29 blades at a rotational speed of 700 rpm has the largest power and torque, namely 15.6 KW power and 210 N/m torque..